Criminal Protection of Credit Cards under UAE Legislation : An Analytical Study - Almidfa, Halima (Journal of Legal Sciences, 2026)
This study addresses the illicit use of credit cards under UAE criminal legislation. It primarily focuses on clarifying the concept of credit cards in terms of their nature, identifying the involved parties, highlighting their advantages, and examining their various types. Additionally, the study explores the legal nature of credit cards and distinguishes them from other similar banking cards.The study delves into a range of illicit practices that jeopardize the secure use of credit cards. It comprehensively explores various criminal offenses, including the unauthorized acquisition of credit card information, credit card forgery, the manufacture of technological devices designed to facilitate such forgery, the fraudulent use of a valid credit card issued in another person's name to seize their funds, and the acceptance of forged credit cards. Furthermore, the study critically examines the legislative measures and criminal provisions enacted under UAE law to combat and address these offenses.